Race Superiority or Racism: A review in the light of World Religions and Islamic Teachings - ., Fatima; Begum, Hashmat (Journal of Islamic and Religious Studies, 2016)
Race represents a specific caste, creed and a generation of a common ancestor. It has been a source of identification among different tribes and group of people, since humankind started life on this earth. With the passage of time different races have started using their racial backgrounds as negative sentiments which created superiority and inferiority complexes among people. Concepts of chosen people aroused in different races which created great gap, differences and hate in the society. The current research work is based upon the concept of superiority in Hinduism and Judaism, which will be further reviewed in the light of Islamic teachings.